Portable borders : performance art and politics on the U.S. frontera since 1984 - Sheren, Ila N. (University of Texas Press, 2015)
After World War II, the concept of borders became unsettled, especially after the rise of subaltern and multicultural studies in the 1980s. Art at the U.S.-Mexico border came to a turning point at the beginning of that decade with the election of U.S. President Ronald Reagan. Beginning with a political history of the border, with an emphasis on the Chicano movement and its art production, Ila Sheren explores the forces behind the shift in thinking about the border in the late twentieth century. Particularly in the world of visual art, borders have come to represent a space of performance rather than a geographical boundary, a cultural terrain meant to be negotiated rather than a physical line. From 1980 forward, Sheren argues, the border became portable through performance and conceptual work. This dematerialization of the physical border after the 1980s worked in two opposite directions?the movement of border thinking to the rest of the world, as well as the importation of ideas to the border itself. Beginning with site-specific conceptual artwork of the 1980s, particularly the performances of the Border Art Workshop/Taller de Arte Fronterizo, Sheren shows how these works reconfigured the border as an active site. Sheren moves on to examine artists such as Guillermo G?mez-Pe?a, Coco Fusco, and Marcos Ramirez "ERRE." Although Sheren places emphasis on the Chicano movement and its art production, this groundbreaking book suggests possibilities for the expansion of the concept of portability to contemporary art projects beyond the region.